HUBUNGAN PERSALINAN KETUBAN PECAH DINI DENGAN KEJADIAN ASFIKSIA PADA BAYI BARU LAHIR DI RUANG PERINATOLOGI RUMAH SAKIT WIJAYA KUSUMA LUMAJANG - Rosadi, Mita; Nur Endah, Yessy; Ermawati, Iit (NHM PRESS, 2023)
Premature rupture of membranes will result in oligohydramnios, resulting in decreased blood flow from mother to fetus so that the baby experiences hypoxia which continues to become asphyxia in newborns. The purpose of this study was to analyze the relationship between premature rupture of membranes and the incidence of asphyxia in newborns in the Perinatology Room at Wijaya Kusuma Hospital Lumajang. The cross-sectional study design was used on 30 respondents in the Perinatology Room of Wijaya Kusuma Lumajang Hospital. This study used questionnaires and observation sheets on the characteristics of the respondents. Analysis using the chi-square test with the result that 16 respondents (53.3%) gave birth to premature rupture of membranes preterm and 11 respondents (36.7%) had asphyxia babies, so there was a significant correlation between premature rupture of membranes and the incidence of asphyxia in newborns in the perinatology room of the hospital wijaya kusuma Lumajang namely p-value 0.000. It is better for future researchers to increase the number of respondents in the study.